Construction of consecutive deletions of the Escherichia coli chromosome - Jun‐ichi Kato; Masayuki Hashimoto (Molecular Systems Biology)
Abstract The minimal set of genetic information necessary and sufficient to sustain a functioning cell contains not only trans‐acting genes, but also cis‐acting chromosomal regions that cannot be complemented by plasmids carrying these regions. In Escherichia coli (E. coli), only one chromosomal region, the origin of replication has been identified to be cis‐acting. We constructed a series of mutants with long‐range deletions, and the chromosomal regions containing trans‐acting essential genes were deleted in the presence of plasmids complementing the deleted genes. The deleted regions cover all regions of the chromosome except for the origin and terminus of replication. The terminus affects cell growth, but is not essential. Our results indicate that the origin of DNA replication is the only vital, unique cis‐acting DNA sequence in the E. coli chromosome necessary for survival.